Comparison Between Effects of Functional Training Program and Conventional Therapy on Postural Control and Functional Mobility in Chronic Stroke - Qurat Ul Ain, Zainab Hassan, Shabana Ashraf, Hafiza Mahjabeen, Fareeha Kousar, Misbah Waris, Sadaf Waris, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To Compare the Effects of Functional Training Program and Conventional Therapy on Postural Control and Functional Mobility in Chronic Stroke Place and duration of Study: This study was conducted in Qureshi Hospital Sahiwal, from September 2019 to March 2020. Methodology: A randomized clinical trial was conducted through non-probability convenient sampling technique in which 12 participants were recruited, randomization was done by Lottery method and participants were divided into 2 groups. Group A received functional training treatment and group B received conventional therapy. Participants of both genders with age 40-65 years were included in study with 6 months of confirmed stroke. Patients with any other neurological disorder or those who were Unable to keep any (Sitting or Standing) position for 30 Second were excluded from the study. Berg balance scale, trunk control measurement scale , 6 Min walk test and time up and go test were used as outcome measuring tools. Pre-treatment and post-treatment readings were taken. And data was analyzed by using SPSS version 21. Results: Mean age and standard deviation of the participants was 48.08±4.833. TUG pre value is 20.25± 2.26 while post treatment value is 15.25±1.14 and pre-value for BBS is 39.75±3.54 while post 48.42±3.2. in 6 MWT pre of the participants was Functional training program improves postural control and functional mobility in chronic stroke patients. Conclusion: It was concluded that functional Training program is better technique to improve patient’s condition as compare to Conventional therapy in TUG and BBS. Both interventions showed non-significant difference on TCMS and 6MWD.